Preparation method of metal zinc negative electrode interface coating of aqueous zinc ion battery

By coating the metal oxide/carbon composite interface coating on the surface of the metal zinc negative electrode of the aqueous zinc ion battery, the problems of corrosion and side reaction of the zinc negative electrode in application are solved, and the safety and cycle life of the battery are improved. The method is environmentally friendly and low-cost, and is suitable for large-scale industrial applications.

CN119627031APending Publication Date: 2025-03-14NANCHANG HANGKONG UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411912156.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In actual application, the metal zinc anode of aqueous zinc ion batteries faces side reaction problems such as metal corrosion, dendrite growth, hydrogen evolution and passivation, which seriously hinders its application in energy storage systems.

Method used

Using an interface coating of a metal oxide/carbon composite material, a composite material with nano-oxide particles anchored on the carbon nanosheets is prepared by mixing the metal salt solution with sulfur-doped carbon dot aqueous solution, and lyophilized. The composite material with nano-oxide particles anchored on the carbon nanosheets is prepared by combining carboxymethyl cellulose to form a uniformly viscous slurry, coated on the surface of zinc foil and vacuum dried.

Benefits of technology

This coating effectively prevents corrosion of zinc foil by the aqueous electrolyte, promotes uniform deposition of Zn2+, inhibits dendrites' growth and side reactions, and improves the safety and cycle life of the battery. At the same time, the method is simple, green and environmentally friendly, low cost, and has the potential for large-scale application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627031A_ABST
    Figure CN119627031A_ABST
Patent Text Reader

Abstract

The preparation method of the metal zinc negative electrode interface coating of the aqueous zinc ion battery specifically comprises the following steps: precipitating and freeze-drying a metal salt solution and a sulfur-doped carbon dot aqueous solution to obtain metal oxide / carbon composite material powder, mixing the metal oxide / carbon composite material powder with carboxymethyl cellulose, coating the surface of zinc foil with the obtained slurry, and performing vacuum drying to obtain the metal zinc negative electrode interface coating of the aqueous zinc ion battery. The metal zinc negative electrode interface coating is obtained. The metal oxide nanoparticles in the metal oxide / carbon composite material are uniformly anchored on the surface of the carbon nanosheet, and the coating can effectively prevent the corrosion of aqueous electrolyte to the zinc foil, can effectively promote the uniform deposition of Zn < 2 + > on the surface of the zinc foil, inhibits dendritic crystal growth and side reaction, improves the safety of the battery, and prolongs the cycle life of the battery. The preparation method is simple, environment-friendly, easy to operate and low in cost, and has the potential of large-scale application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a metallic zinc negative electrode interface coating of an aqueous zinc ion battery, and specifically belongs to the technical field of new energy materials. Background Art

[0002] Aqueous zinc-ion batteries are considered to be one of the most promising batteries in the field of large-scale energy storage due to their advantages such as high capacity, high safety and low cost. However, the metal zinc anode of aqueous zinc-ion batteries currently faces side reaction problems such as metal corrosion, dendrite growth, hydrogen evolution and passivation in practical applications, which seriously hinders the application of aqueous zinc-ion batteries in energy storage systems. Therefore, modifying and optimizing the metal zinc anode is one of the key technologies to achieve large-scale, efficient, safe and high energy density energy storage in aqueous zinc-ion batteries.

[0003] At present, constructing anode surface coating is one of the most common strategies for the modification and optimization of metal zinc anode. This method has attracted widespread attention because of its simple operation, obvious modification effect and potential for large-scale industrial application. The coating materials used are mainly: 1) conductive protective layer (such as carbon (Journal of Energy Chemistry 2022, 75, 135-153.), metal (Journal of Power Sources 2022, 525, 231122.), etc.); such conductive protective layer can adjust the uniformity of the electric field distribution on the surface of the metal zinc anode, thereby inducing uniform deposition of Zn2+; however, during long-term cycling, zinc may still penetrate the conductive protective layer and the separator and directly contact the positive electrode to cause a short circuit, leading to safety problems in the battery. 2) Non-conductive protective layers (such as metal oxide TiO2 (patent CN113540390B), MOF (patent CN113258070B), Prussian blue (CN119009183A) and CaCO3, etc.) can be used to prevent direct contact between the zinc negative electrode and the solvent, thereby effectively inhibiting the occurrence of side reactions; however, these non-conductive protective layers will significantly reduce the ion and electron transmission efficiency on the surface of the metal zinc negative electrode and reduce the power density of the battery. 3) Polymer coatings (such as polydopamine (Wang Tingting. Design and performance study of coatings for zinc negative electrodes of zinc ion batteries. Master's thesis, 2022. North China University of Technology), polyacrylamide (patent CN117457843A), polyimide (Wang Lang. Preparation and research of zinc negative electrode coatings for aqueous zinc ion batteries. Master's thesis, 2023, Dalian Maritime University), polysaccharides (patent CN117293412A), etc.); polymer coatings can effectively inhibit the growth of dendrites, while isolating the contact between the electrolyte and the negative electrode to prevent corrosion of the zinc negative electrode; however, polymer coatings often require the use of organic solvents during the preparation process and coating film formation process, which can easily cause environmental pollution; and the mechanical strength of a single polymer coating is poor, making it difficult to ensure the long-cycle stability of the metal zinc negative electrode. Therefore, in response to the above technical problems, the present invention proposes a method for preparing a metal zinc negative electrode interface coating for an aqueous zinc ion battery, aiming to provide a simple, green and efficient metal zinc negative electrode protection method to meet the requirements of actual industrial production. Summary of the invention

[0004] In view of the above situation, the present invention provides a method for preparing a metal zinc negative electrode interface coating of an aqueous zinc ion battery. The present invention provides a method for preparing a metal zinc negative electrode interface coating of an aqueous zinc ion battery, comprising the following steps: Step 1: adding a metal salt solution to a sulfur-doped carbon dot aqueous solution, stirring and standing to obtain a precipitate; Step 2: After freeze-drying the precipitate, place it in a tube furnace for heat treatment to obtain a powder of the metal oxide / carbon composite material; Step 3: Mix the powder of the metal oxide / carbon composite material and carboxymethyl cellulose in deionized water in proportion, and stir vigorously to obtain a uniform and viscous slurry; Step 4: Apply the slurry evenly on the surface of the zinc foil and use a scraper to accurately control the thickness of the slurry; Step 5: The coated zinc foil is vacuum dried to obtain a metallic zinc negative electrode interface coating.

[0005] The metal salt is at least one of lanthanum (III) nitrate, cerium (II) nitrate, cerium (III) nitrate, yttrium (III) nitrate, zirconium (IV) nitrate, samarium (III) nitrate, europium (III) nitrate, gadolinium (III) nitrate and their corresponding salts containing crystal water.

[0006] The atomic fraction of sulfur in the sulfur-doped carbon dots is about 6-10%.

[0007] The heat treatment temperature is 600-900° C., the heating rate is 2-5° C. / min, the heat preservation time is 2-10 hours, and the atmosphere is inert gas.

[0008] The mass ratio of the metal oxide to carbon in the metal oxide / carbon composite material is 1-3:1.

[0009] In the slurry, the mass ratio of the metal oxide / carbon composite material to the carboxymethyl cellulose is 3-6:1.

[0010] The vacuum drying is carried out at a temperature of 60° C. for 8 to 16 hours.

[0011] The thickness of the metal zinc negative electrode interface coating is 5-20 μm.

[0012] Beneficial effects of the present invention: The present invention provides a metal zinc negative electrode interface coating for an aqueous zinc ion battery and a preparation method thereof. The metal oxide nanoparticles in the metal oxide / carbon composite material used as the metal zinc negative electrode interface coating are uniformly anchored on the surface of the carbon nanosheet, wherein the carbon nanosheet has good electrical conductivity and the metal oxide has high zinc affinity. The coating can effectively prevent the corrosion of the aqueous electrolyte to the zinc foil. In addition, the coating can also effectively promote the Zn 2+ The uniform deposition of zinc on the surface of the zinc foil inhibits the growth of dendrites and the occurrence of side reactions, thereby improving the safety and cycle life of the battery. The preparation method of the present invention is simple, green and environmentally friendly, easy to operate, low in cost, and has the potential for large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 : Transmission electron microscopy image of the cerium oxide / carbon composite material (CeO2 / C) prepared in Example 1 of the present invention; Figure 2: Scanning electron microscope image of the cerium oxide / carbon composite material (CeO2 / C) coating on the zinc foil interface in Example 1 of the present invention; Figure 3 : Bare zinc symmetric battery and CeO2 / C coating modified zinc symmetric battery of Example 1 of the present invention at 1 mA / cm 2 、1mAh / cm 2 Voltage-time graph under test conditions. DETAILED DESCRIPTION

[0014] Example 1 The steps of the method for preparing the metallic zinc negative electrode interface coating of the aqueous zinc ion battery of this embodiment are as follows: Step 1: 0.01 mol of cerium (II) nitrate is prepared into a 30 mL solution, and then added into a 30 mL 10 g / L sulfur-doped carbon dot aqueous solution, and stirred and allowed to stand to obtain a precipitate; Step 2: After freeze-drying, the collected precipitate is placed in a tube furnace for heat treatment to obtain a cerium oxide / carbon composite material (CeO2 / C) powder; wherein the heat treatment temperature is 600°C, the heating rate is 5°C / min, the holding time is 6 hours, the atmosphere is an inert argon atmosphere, and the atmosphere flow rate is 200CC / min; the mass ratio of cerium oxide to carbon in the cerium oxide / carbon composite material is 7:3; Step 3: mixing the cerium oxide / carbon composite material powder and carboxymethyl cellulose in deionized water at a mass ratio of 4:1, and stirring vigorously to obtain a uniform and viscous slurry; Step 4: Apply the slurry evenly on the surface of the zinc foil and use a scraper to accurately control the thickness of the slurry; Step 5: Place the coated zinc foil in a vacuum drying oven at 60°C and dry it for 12 hours to obtain a CeO2 / C coating with a thickness of 15 μm on the metal zinc negative electrode interface.

[0015] The metal zinc negative electrode with CeO2 / C coating was applied to aqueous zinc-ion batteries, and a blank control experiment (bare metal zinc negative electrode without CeO2 / C coating) was carried out for charge and discharge cycles; the cycle life of the bare zinc││bare zinc-zinc symmetric battery in the blank control experiment was less than 200 hours, while the zinc││zinc symmetric battery with CeO2 / C coating on the interface still maintained good stability after 1000 hours of cycling.

[0016] Figure 1 The transmission electron microscopy image of the cerium oxide / carbon composite material (CeO2 / C) prepared in Example 1 is shown in FIG. Figure 1 It can be seen that nano-cerium oxide is anchored on the surface of carbon nanosheets.

[0017] Figure 2This is a scanning electron microscope image of the cerium oxide / carbon composite material (CeO2 / C) coating on the zinc foil surface prepared in Example 1. Figure 2 It can be seen that the coating is evenly coated on the surface of the zinc foil.

[0018] Figure 3 The zinc symmetric battery prepared in Example 1 was 2 、1mAh / cm 2 The voltage-time curve under the test conditions shows that the cycle life of the zinc-zinc symmetric battery in the blank control experiment is less than 200 hours, while the zinc-zinc symmetric battery coated with CeO2 / C coating still maintains good stability after 1000 hours of cycling.

[0019] Example 2 The steps of the method for preparing the metallic zinc negative electrode interface coating of the aqueous zinc ion battery of this embodiment are as follows: Step 1: 0.02 mol of lanthanum (III) nitrate was prepared into 30 mL of solution and added into 50 mL of 10 g / L sulfur-doped carbon dot aqueous solution, and the mixture was stirred and allowed to stand to obtain a precipitate; Step 2: Collect the precipitate, freeze-dry it, and place it in a tube furnace for heat treatment to prepare lanthanum oxide / carbon composite material (La2O3 / C) powder; wherein the heat treatment temperature is 700°C, the heating rate is 4°C / min, the holding time is 8 hours, the atmosphere is an inert nitrogen atmosphere, and the atmosphere flow rate is 150CC / min; the mass ratio of lanthanum oxide to carbon in the composite material is 2:1; Step 3: mixing lanthanum oxide / carbon composite material powder and carboxymethyl cellulose in deionized water at a mass ratio of 5:1, and stirring vigorously to obtain a uniform and viscous slurry; Step 4: Apply the slurry evenly on the surface of the zinc foil and use a scraper to accurately control the thickness of the slurry; Step 5: Place the coated zinc foil in a vacuum drying oven at 80° C. and dry for 12 hours to obtain a coating with a thickness of 10 μm.

[0020] The metal zinc negative electrode coated with La2O3 / C was applied to aqueous zinc-ion batteries, and a blank control experiment (bare metal zinc negative electrode) was carried out for charge and discharge cycles. The cycle life of the bare zinc││bare zinc symmetric battery in the blank control experiment was less than 200 hours, while the zinc││zinc symmetric battery coated with La2O3 / C coating still maintained good stability after 1500 hours of cycling.

[0021] Example 3 The steps of the method for preparing the metallic zinc negative electrode interface coating of the aqueous zinc ion battery of this embodiment are as follows: Step 1: 0.03 mol of gadolinium (III) nitrate was prepared into 30 mL solution and added into 60 mL of 10 g / L sulfur-doped carbon dot aqueous solution, and the mixture was stirred and allowed to stand to obtain a precipitate; Step 2: Collect the precipitate, freeze-dry it, and then place it in a tube furnace for heat treatment to prepare gadolinium oxide / carbon composite material (Gd2O3 / C) powder; wherein the heat treatment temperature is 900°C, the heating rate is 5°C / min, the holding time is 6 hours, the atmosphere is an inert argon atmosphere, and the atmosphere flow rate is 200 CC / min; the mass ratio of gadolinium oxide to carbon in the composite material is 5.5:3; Step 3: mixing the gadolinium oxide / carbon composite material powder and carboxymethyl cellulose in deionized water at a mass ratio of 6:1, and stirring vigorously to obtain a uniform and viscous slurry; Step 4: Apply the slurry evenly on the surface of the zinc foil and use a scraper to accurately control the thickness of the slurry; Step 5: Place the coated zinc foil in a vacuum drying oven at 70° C. and dry for 10 hours. The resulting coating has a thickness of 20 μm.

[0022] The metal zinc negative electrode coated with Gd2O3 / C was applied to aqueous zinc-ion batteries, and a blank control experiment (bare metal zinc negative electrode) was carried out for charge and discharge cycles. The cycle life of the bare zinc││bare zinc symmetric battery in the blank control experiment was less than 200 hours, while the zinc││zinc symmetric battery coated with Gd2O3 / C coating still maintained good stability after 1300 hours of cycling.

Claims

1. A method for preparing a metallic zinc negative electrode interface coating for an aqueous zinc ion battery, characterized in that: The method for preparing the metallic zinc negative electrode interface coating comprises the following steps: Step 1: adding a metal salt solution to a sulfur-doped carbon dot aqueous solution, stirring and standing to obtain a precipitate; Step 2: After freeze-drying the precipitate, place it in a tube furnace for heat treatment to obtain a powder of the metal oxide / carbon composite material; Step 3: Mix the powder of the metal oxide / carbon composite material and carboxymethyl cellulose in deionized water in proportion, and stir vigorously to obtain a uniform and viscous slurry; Step 4: Apply the slurry evenly on the surface of the zinc foil and use a scraper to accurately control the thickness of the slurry; Step 5: The coated zinc foil is vacuum dried to obtain a metallic zinc negative electrode interface coating.

2. The method for preparing a metallic zinc negative electrode interface coating of an aqueous zinc ion battery according to claim 1, wherein: The metal salt is at least one of lanthanum (III) nitrate, cerium (II) nitrate, cerium (III) nitrate, yttrium (III) nitrate, zirconium (IV) nitrate, samarium (III) nitrate, europium (III) nitrate, gadolinium (III) nitrate and their corresponding salts containing crystal water.

3. According to claim 1, a kind of aqueous zinc ion battery metal zinc negative electrode interface coating and preparation method thereof, it is characterized in that: The atomic fraction of sulfur in the sulfur-doped carbon dots is about 6-10%.

4. The method for preparing a metallic zinc negative electrode interface coating of an aqueous zinc ion battery according to claim 1, wherein: The heat treatment temperature is 600-900° C., the heating rate is 2-5° C. / min, the holding time is 2-10 hours, the atmosphere is an inert atmosphere, and the atmosphere flow rate is 100-200 CC / min.

5. The method for preparing a metallic zinc negative electrode interface coating of an aqueous zinc ion battery according to claim 1, wherein: The mass ratio of the metal oxide to carbon in the metal oxide / carbon composite material is 1-3:

1.

6. The method for preparing a metallic zinc negative electrode interface coating of an aqueous zinc ion battery according to claim 1, characterized in that: In the slurry, the mass ratio of the metal oxide / carbon composite material to the carboxymethyl cellulose is 3-6:

1.

7. The method for preparing a metallic zinc negative electrode interface coating of an aqueous zinc ion battery according to claim 1, characterized in that: The vacuum drying is carried out at a temperature of 60° C. for 8 to 16 hours.

8. The method for preparing a metallic zinc negative electrode interface coating of an aqueous zinc ion battery according to claim 1, characterized in that: The thickness of the metal zinc negative electrode interface coating is 5-20 μm.

Citation Information

Patent Citations

  • Metal oxide-carbon composite material regulated and controlled by carbon dots as well as preparation method and application of metal oxide-carbon composite material

    CN114864889A

  • Zinc negative electrode material with inorganic oxide interface protection layer and preparation and application thereof

    CN116598444A

  • Composite zinc metal negative electrode for aqueous ion battery as well as preparation and application of composite zinc metal negative electrode

    CN117954569A